Judge's Considerations in the Matter of Changing the Status of Whistleblower to Justice Collaborator (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This study discusses the judge's considerations in the case of Daud Ndakularak who initially had the status of a whistleblower and then switched to become a justice collaborator in a corruption case. The focus of the research lies in the analysis of juridical and non-juridical considerations of judges, as well as the application of the provisions of the Supreme Court Circular Letter Number 4 of 2011 regarding the requirements for the change in status.Purposes of the Research: This study aims to analyze the judge's review of the change in the status of Whistleblower to Justice Collaborator on the decision of Daud Ndakularak.Methods of the Research: The research method used is normative juridical with a case study approach, through the analysis of court decisions and related laws and regulations.Findings of the Research: The panel of judges considers both juridical and non-juridical aspects before deciding the case. Juridical considerations include the analysis of the indictment, demands, evidence, and elements of the article charged, while non-juridical considerations include circumstances that are aggravating and mitigating to the defendant. The judge also referred to the provisions of the Supreme Court Circular Letter Number 4 of 2011 in assessing the feasibility of changing the status of whistleblower to justice collaborator. The final verdict revealed that the defendant was legally proven innocent in terms of committing a criminal act of corruption as contained in the primary indictment, therefore the defendant was given freedom from the indictment. This reveals that the judge's assessment of this case or issue is in accordance with the applicable legal provisions.